Nonpharmacologic Interventions for Reducing Blood Pressure in Adults With Prehypertension to Established Hypertension - Fu, Jinming; Liu, Yupeng; Zhang, Lei; Zhou, Lu; Li, Dapeng; Quan, Hude; Zhu, Lin; Hu, Fulan; Li, Xia; Meng, Shuhan; Yan, Ran; Zhao, Suhua; et al. (Journal of the American Heart Association, 2020)
Background Nonpharmacologic interventions that modify lifestyle can lower blood pressure (BP) and have been assessed in numerous randomized controlled trials and pairwise meta-analyses. It is still unclear which intervention would be most efficacious. Methods and Results Bayesian network meta-analyses were performed to estimate the comparative effectiveness of different interventions for lowering BP. From 60 166 potentially relevant articles, 120 eligible articles (14 923 participants) with a median follow-up of 12 weeks, assessing 22 nonpharmacologic interventions, were included. According to the surface under the cumulative ranking probabilities and Grading of Recommendations Assessment, Development and Evaluation (GRADE) quality of evidence, for adults with prehypertension to established hypertension, high-quality evidence indicated that the Dietary Approach to Stop Hypertension (DASH) was superior to usual care and all other nonpharmacologic interventions in lowering systolic BP (weighted mean difference, 6.97 mm Hg; 95% credible interval, 4.50-9.47) and diastolic BP (weighted mean difference, 3.54 mm Hg; 95% credible interval, 1.80-5.28). Compared with usual care, moderate- to high-quality evidence indicated that aerobic exercise, isometric training, low-sodium and high-potassium salt, comprehensive lifestyle modification, breathing-control, and meditation could lower systolic BP and diastolic BP. For patients with hypertension, moderate- to high-quality evidence suggested that the interventions listed (except comprehensive lifestyle modification) were associated with greater systolic BP and diastolic BP reduction than usual care; salt restriction was also effective in lowering both systolic BP and diastolic BP. Among overweight and obese participants, low-calorie diet and low-calorie diet plus exercise could lower more BP than exercise. Conclusions DASH might be the most effective intervention in lowering BP for adults with prehypertension to established hypertension. Aerobic exercise, isometric training, low-sodium and high-potassium salt, comprehensive lifestyle modification, salt restriction, breathing-control, meditation and low-calorie diet also have obvious effects on BP reduction.